2021
DOI: 10.1073/pnas.2018072118
|View full text |Cite
|
Sign up to set email alerts
|

Observation of liquid glass in suspensions of ellipsoidal colloids

Abstract: Despite the omnipresence of colloidal suspensions, little is known about the influence of colloid shape on phase transformations, especially in nonequilibrium. To date, real-space imaging results at high concentrations have been limited to systems composed of spherical colloids. In most natural and technical systems, however, particles are nonspherical, and their structural dynamics are determined by translational and rotational degrees of freedom. Using confocal microscopy of fluorescently labeled core–shell … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 60 publications
(78 reference statements)
1
17
0
Order By: Relevance
“…Since we experimentally established which residues are attractively interacting during dense phase formation, we decided to explore a plausible topological network of GY-23 that might model the aging soft glass network observed in other coacervates . The nonequilibrium thermodynamic state of a glass, including soft glassy liquids and glassy states in folding proteins, is a phenomenon of physical aging that manifests by a reduction in volume and enthalpy, until a new equilibrium is established at the aging temperature . Unfortunately, the time-scale for equilibration becomes very long, ranging from minutes to years and preventing direct computational exploration of the available and evolving molecular configurational space.…”
Section: Resultsmentioning
confidence: 99%
“…Since we experimentally established which residues are attractively interacting during dense phase formation, we decided to explore a plausible topological network of GY-23 that might model the aging soft glass network observed in other coacervates . The nonequilibrium thermodynamic state of a glass, including soft glassy liquids and glassy states in folding proteins, is a phenomenon of physical aging that manifests by a reduction in volume and enthalpy, until a new equilibrium is established at the aging temperature . Unfortunately, the time-scale for equilibration becomes very long, ranging from minutes to years and preventing direct computational exploration of the available and evolving molecular configurational space.…”
Section: Resultsmentioning
confidence: 99%
“…This is the case, for instance, in dense and highly asymmetric colloidal mixtures of hard spheres 58 and also in suspensions where the pair interactions between colloids depend on particle's orientations. [59][60][61] An interesting question that arises in this context, thus, is if the application of the NE-SCGLE theory to a simple model that incorporates, for example, rotational-translational dynamical coupling (or, alternatively, coupling in the dynamics of multiple species) could also serve to extend TNM's model of aging to such more complex conditions.…”
Section: The Tnm Model For Systems With Rotational-translational Dyna...mentioning
confidence: 99%
“…Recently, liquid glasses were discovered experimentally in suspensions of ellipsoidal colloids that similarly to liquid crystals demonstrate glass-like properties before being melted [48]. It is well known from earlier investigations that emulsions exhibit fractal structures at small sizes [49]; however, structural imaging at high concentrations has been limited to systems composed of spherical colloids.…”
Section: Cpt Of Glass Transitionmentioning
confidence: 99%
“…It is well known from earlier investigations that emulsions exhibit fractal structures at small sizes [49]; however, structural imaging at high concentrations has been limited to systems composed of spherical colloids. The authors of [48] revealed that suspensions of ellipsoidal colloids form an unexpected state of matter, a liquid glass in which rotations are frozen while translations remain fluid. The nematic precursors were characteristic structural elements of this state, and the mutual obstruction of these ramified clusters prevented liquid crystalline order.…”
Section: Cpt Of Glass Transitionmentioning
confidence: 99%